ERGONOMIC FURNITURE STUDY IN CAFÉ GREENS & BEANTOWARDS USER COMFORT - Feria Riandy; Astrid Austranti Yuwono; Gai Suhardja (Ide dan Dialog Desain Indonesia (Idealog), 2020)
Café has become a choice of places to eat out that is quite demanded by various groups. Other than to eat, many people spend their time at cafés for meeting, work assignments, or just to relax. Therefore furniture in the café especially tables and chairs must have the appropriate ergonomics so that visitors can feel comfortable when they are at the café. Study related to the ergonomics of the dining area furniture at Greens and Bean café is conducted to determine the level of comfort felt by the visitors. This research used descriptive qualitative research methods with data collection technique in the form of observation, questionnaires, and direct measurement. Through this research an evaluation about ergonomics and comfortable dining area furniture will be obtained. Keywords: comfort, ergonomics, café, furniture